Decline of arable flora diversity in Istria (from the year 2005 to the year 2017) - Štefanić, Edita (Array, 2018)
Changes in floristic composition of weed flora were assessed comparing two phytocoenological surveys carried out during vegetation seasons in 2005 and in 2017 on the Istrian Peninsula. A total of 50 fields (row crops, cereals, alfalfa fields, orchards/vineyards and ruderal areas) were surveyed for each of the sampling time using Braun-Blanquet cover-abundance scale. Altogether 175 vascular plant species were recognized in both investigations. The most abundant species in 2005 were Avena fatua, Setaria verticilata, Lolium multiflorum and Veronica persica. In the recent survey these species became very rare or were even not detected in some habitats. In contrast, some species with very low relative abundance or not recorded in the earlier survey were found abundant in 2017. These are: Pastinaca sativa, Conyza canadensis, Picris echioides, Polygonum aviculare, and Heliotropium europaeum. The species richness was significantly higher in the earlier survey when 143 (82%) weeds were detected compared to only 97 species (55%) found in 2017. Only 64 species were found in both surveys, and these were considered frequent weeds. The comparison of weed communities from the earlier to the recent survey reflects the reduction of the weed flora at the regional scale, as well as at the field scale. The mean values of Shannon-Wiener diversity index were also higher in the earlier period and it decreased over time, particularly in row crops, cereals and ruderal habitats. This decrease was related to decline of species richness, and to the increase in inequality in the relative abundance of species. On the whole, canonical correspondence analysis indicated the major variations in species composition between different habitats.